1994
DOI: 10.1002/bit.260440407
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of pristinamycins in aqueous two‐phase systems: A first step toward the development of antibiotic production by extractive fermentation

Abstract: The partitioning of pristinamycins was studied in dextran and polyethylene glycol (PEG) aqueous two-phases systems. Pristinamycins partitioned preferentially into the PEG-rich top phase. The partition coefficient was independent of molar mass of PEG and dextran and of antibiotic concentration, but, increased exponentially with the tieline length of the system. Partition of pristinamycins was greatly improved when fatty acids esters of PEG were mixed with PEG. In such mixtures, the partition of coefficient incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Therefore, it is clearly suggested that pristinamycins production was not associated with the mycelia growth, and it might be a typical example of a growth-disassociated product. On the other hand, because of the degradation of pritinamycins by enzymes, a limitation of the antibiotic production was observed after reaching the maximum, which was in agreement with the previous report [35]. The reducing sugar concentration slowly increased in the first 29 h and decreased thereafter until to 1.29 g/L.…”
Section: Time Course Of Pristinamycins Fermentationsupporting
confidence: 90%
“…Therefore, it is clearly suggested that pristinamycins production was not associated with the mycelia growth, and it might be a typical example of a growth-disassociated product. On the other hand, because of the degradation of pritinamycins by enzymes, a limitation of the antibiotic production was observed after reaching the maximum, which was in agreement with the previous report [35]. The reducing sugar concentration slowly increased in the first 29 h and decreased thereafter until to 1.29 g/L.…”
Section: Time Course Of Pristinamycins Fermentationsupporting
confidence: 90%
“…Yang et al [8] showed that ATPS were able to extract cephalosporin C from whole culture medium, separating early in the process, cells and desacetyl cephalosporin C, a by-product with a molecular structure close to the target molecule. Paquet et al [9] studied partitioning of prestinamycins from whole culture medium and observed that cells were confined into the bottom phase and prestinamycins partitioned to the top phase.…”
Section: Introductionmentioning
confidence: 98%
“…The partitioning behaviour of cephalexin and 7‐ADCA was investigated in ATPS consisting of ammonium sulfate and PEG with different molecular weights. The compositions of the ATPS system were designed to produce the same TLL to assess the influence of PEG molecular weight 11. TLL was calculated according to:20 where W is the concentration of PEG or ammonium sulfate (A) in the top (T) or bottom (B) phase.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing published data concerning the partition of low‐molecular‐weight substances, however, indicate that it is possible for them to partition unequally in ATPS 9. 10 Some papers also reported that bioconversion of low‐molecular‐weight substances in ATPS is practicable 11–14. Bioconversion in ATPS had been studied in the production of oligosaccharides,14 peptides,15 aspartame derivatives,16 etc.…”
Section: Introductionmentioning
confidence: 99%